Comparison of the analgesic effects of ultrasound-guided erector spinae plane block and quadratus lumborum block: a systematic review and meta-analysis - Wu, Lin; Zhang, Weiyi; Wei, Yiyong; Zhang, Donghang (Frontiers in Pharmacology, 2025)
BackgroundErector spinae plane block (ESPB) and quadratus lumborum block (QLB) are commonly used for perioperative analgesia in various surgeries. An increasing number of randomized controlled trials (RCTs) have compared the analgesic effect and safety of ESPB with those of QLB, but the conclusions are controversial. This study was designed to identify whether ultrasound-guided ESPB was better than the QLB for postoperative analgesia.MethodsTo identify RCTs comparing ESPB with QLB for postoperative analgesia, we searched PubMed, Embase, the Cochrane Library, and Web of Science. The primary outcome was postoperative analgesic consumption over 24 h. The secondary outcomes included the time to the first analgesic request, postoperative resting pain scores, block performance time, postoperative rescue analgesia rate, incidence of complications, and postoperative satisfaction. RevMan 5.4 software was used in the analysis. Subgroup analysis and sensitivity analysis were performed to explore the source of heterogeneity and test the reliability of the pooled results. The quality of evidence was systematically assessed via the GRADE evaluation.ResultsTwenty-seven studies involving 1942 patients were included. Compared with QLB, ESPB consumed fewer 24-h postoperative analgesics (WMD, −4.03; 95% CI, −6.25 to −1.82; P = 0.0004; moderate quality of evidence), spent less time performing blocks (WMD, −1.55; 95% CI, −2.68 to −0.41; P = 0.008; moderate quality of evidence), and had a lower incidence of postoperative nausea and vomiting (RR, 0.72; 95% CI, 0.58 to 0.91; P = 0.006; high quality of evidence). ESPB and QLB did not significantly differ in terms of time to the first analgesic request (WMD, −0.12; 95% CI, −0.47 to 0.22; P = 0.48; moderate quality of evidence) or postoperative resting pain scores at 6 h, 12 h, and 24 h (6 h: SMD, 0.08; 95% CI, −0.27 to 0.24; P = 0.66; moderate quality of evidence; 12 h: SMD, 0.13; 95% CI, −0.28 to 0.55; P = 0.53; moderate quality of evidence; 24 h: SMD, −0.02; 95% CI, −0.22 to 0.18; P = 0.87; moderate quality of evidence).ConclusionModerate-to high-quality evidence indicates that ESPB is superior to QLB for postoperative analgesia because of less postoperative analgesic consumption, faster block performance and a lower incidence of postoperative nausea and vomiting.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024607988.